1992
DOI: 10.1103/physrevb.45.10902
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and optical properties of europium-activated yttrium oxide phosphor

Abstract: The electronic structure and optical properties of a red phosphor, Y203.Eu, have been studied using the first-principles molecular-orbital and band-structure methods. Using the calculated one-electron energy levels, several properties of the host material and properties of the phosphor based on host-impurity interactions have been explained. However, it has been found that the luminescence properties of Eu + require the spin-orbit effects to be included in the computational methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(59 citation statements)
references
References 25 publications
0
59
0
Order By: Relevance
“…It was found that the full width at half maximum (FWHM) decreases almost 50% for films annealed at 973 K, when lithium doping was done. This is an indication of the better crystallization and larger grain size and can be regarded as a result of the flux effect of Li + ions during the growth process, which plays a role in effective promotion of the incorporation of Eu 2 O 3 and Gd 2 O 3 as well as Li + ions themselves into the host lattice [36].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the full width at half maximum (FWHM) decreases almost 50% for films annealed at 973 K, when lithium doping was done. This is an indication of the better crystallization and larger grain size and can be regarded as a result of the flux effect of Li + ions during the growth process, which plays a role in effective promotion of the incorporation of Eu 2 O 3 and Gd 2 O 3 as well as Li + ions themselves into the host lattice [36].…”
Section: Methodsmentioning
confidence: 99%
“…Among these factors composition could be one of the lead breakthroughs for increased brightness of Gd 2 O 3 :Eu 3+ thin films. It is well known that even in very small quantities, the Li + coactivators frequently play an important role in the enhancement of the luminescent efficiency of phosphors [4,19]. Yi [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoluminescence spectra of the thin films included two strong peaks which originated from two transitions of 5 D 0 → 7 F 1 (594 nm) and 5 D 0 → 7 F 2 (617 nm) of levels of Eu 3+ ions [38,39]. The emission peak intensities of the two transitions increase with increasing annealing temperature, due to improved crystallinity of the thin films, resulting in higher oscillating strengths for optical transitions [40,41]. At higher temperature, Eu 3+ ions can arrive at real lattice sites more easily, thus this leads to enhanced activation of Eu 3+ ions [42].…”
Section: Photoluminescence Properties Of (Bi Ln) 4 Ti 3 O 12 Thin Filmsmentioning
confidence: 99%
“…The polarization enhancement by La 3+ substitution can be attributed to crystallization improvement of the thin films which has been confirmed by XRD and SEM. In addition, better crystallinity can also result in strong photoluminescence due to higher oscillating strengths for the optical transitions [41].…”
Section: Photoluminescence Properties Of (Bi Ln) 4 Ti 3 O 12 Thin Filmsmentioning
confidence: 99%